2013
DOI: 10.3174/ajnr.a3743
|View full text |Cite
|
Sign up to set email alerts
|

An Exponential Growth in Incidence of Thyroid Cancer: Trends and Impact of CT Imaging

Abstract: BACKGROUND AND PURPOSE:Workup of incidental thyroid nodules detected on CT imaging could be contributing to the increased diagnosis of small thyroid cancers. The purpose of this study was to evaluate recent trends in the incidence of thyroid cancer, and to determine the relationship between annual CT imaging volume and rate of thyroid cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…This finding may also be explained, in part, by the fact that CT utilization has increased rapidly in the United States, at a rate greater than sonography, and utilization of CT scanning exceeds sonography. 24,25 Hoang et al 24 reported a strong linear relationship between new cases of subcentimeter thyroid cancer and the number of CT scans per year, suggesting that the increase in CT scans may account for increased detection of incidental thyroid cancers. The fact that nearly half of ITNs that proceed to surgery are detected on CT underscores the need for guidelines to reduce the potentially unnecessary work-up of CT-detected ITN.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may also be explained, in part, by the fact that CT utilization has increased rapidly in the United States, at a rate greater than sonography, and utilization of CT scanning exceeds sonography. 24,25 Hoang et al 24 reported a strong linear relationship between new cases of subcentimeter thyroid cancer and the number of CT scans per year, suggesting that the increase in CT scans may account for increased detection of incidental thyroid cancers. The fact that nearly half of ITNs that proceed to surgery are detected on CT underscores the need for guidelines to reduce the potentially unnecessary work-up of CT-detected ITN.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplastic carcinoma is an aggressive undifferentiated tumor typically occurring in the elderly with a median survival of 9 weeks and a 5-year survival of 7% (9). The most common histology is papillary carcinoma, which represents 88% of all thyroid malignancies (10).…”
Section: What Are the Essential Facts About Thyroid Cancer?mentioning
confidence: 99%
“…Small papillary thyroid cancers are associated with an excellent prognosis. According to the 2009 Surveillance, Epidemiology, and End Results Program (SEER) database, the 10-year survival rate for a 10-14 mm thyroid cancer is 99.6% without nodal metastases and 98.9% with nodal metastases (3). Thyroid cancer may also remain subclinical, such that many patients die with, rather than from, thyroid cancer, which was demonstrated in one postmortem study in which small foci of thyroid cancer were present in the thyroid glands of 36% of patients who died from other causes (18).…”
Section: Discussionmentioning
confidence: 99%
“…ITN have a low malignancy rate, and subclinical thyroid cancers generally demonstrate indolent behavior (1)(2)(3). Still, ITN pose a management dilemma for radiologists and clinicians who do not wish to overinvestigate benign nodules but remain concerned about missing a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%